Development of a motorized cutter (electro-mechanical part) and integration system - Nadirah, Ismail (2008)
A motorized cutter been designed to use in harvesting fresh fruit bunches especially during fruit season. The main reason for the motorized cutter been designed is to make it easier for the users or consumers operating the cutter without using high energy. The motorized cutter had been support with 24V DC motor, 24V rechargeable battery, cable and other electrical components. H-bridge concept being used in electrical circuit so that the motor rotor can rotate clockwise or anti clockwise when the push button is pressed.